Screw material extrusion of super soft thermoplastic elastomer for additive manufacturing of inflatables - Albert Curmi; Arif Rochman (Virtual and Physical Prototyping)
This study managed to successfully 3D print inflatables using 32 Shore 00 soft thermoplastic elastomer (TPE), granules. This TPE is softer than any previously 3D printed TPE in literature and was achieved by using an in-house developed, desktop screw extruder. The first step involved characterising the TPE using various techniques to determine optimal printing parameters and material handling conditions. The second step dealt with extruder calibration for 3D printing and then the production of tensile specimens in the XY and Z orientations. A maximum strain without failure of 3365% was achieved at XY orientation at 310°C. In contrast, the highest strain of the Z orientation was recorded at 290°C reaching 2330 ± 139% at failure. Finally, the system was used to 3D print cubic and hexagonal prisms of different sizes, and then each was inflated till failure. Video procedural analysis of the inflation process determined that the highest, biaxial strain at failure reached 590%. These results enable the development of an innovative elastic inflatable actuator (EIA) to successfully pick and place fragile objects using soft, lightly pressurised inflatables. In conclusion, a production method for prototyping and general fabrication of large expansion AM inflatables has been established.